Anti-Money Laundering (AML) Information Technology Strategies in Cross-Border Payment Systems - Haiying Yi (Law and Economy, 2024)
This paper aims to explore the application of information technology in the implementation of anti-money laundering (AML) measures within cross-border payment systems, analyzing how it enhances the compliance of financial institutions and strengthens the effectiveness of financial regulation. By examining the use of information technologies such as big data analytics, artificial intelligence, and blockchain in the field of AML, this paper reveals how these technologies assist financial institutions in more effectively identifying and preventing money laundering activities. Additionally, the paper discusses the challenges that may be encountered in the implementation of these technologies, such as data privacy protection, technical compatibility, and security issues, and proposes corresponding countermeasures and suggestions. The research findings indicate that, despite challenges, the application of information technology is of great significance for improving the AML compliance and regulatory efficiency of cross-border payment systems, providing new perspectives and solutions for financial regulatory authorities and institutions.